Poetic advertisement in the ancient Arab heritage (Journal of the College of Basic Education, 2023)
man lives today; In a sea of media and advertising - truthful orliars To this extent or that - depending on what is read, audio and visual, in all its forms.different; book, magazine or newspaper; broadcast or recorded; cinema, television, or the InternetCompact disk...etc. Was it the old Arab? an exhibition for the media and advertising and what is between theminterference?This is the question that this research tried to answer. Extrapolation of what is available from what has been achievedancient Arabic poetry; in which the media and advertising phenomena seemed clear, to captureResearch aspects of political and social advertising; interested in marriage or work advertisements; Exceptabout commercial advertising, and some of this advertisement was successful; achieves its objectives in whole or in part;In addition to the counter declaration; whether he succeeded in achieving his goals or not, and what was in thisThe research studies models that have similarities and isotopes that are suitable for study, if there is an interested or specialist in them.He would write a master's thesis or a doctoral dissertation in it, or even write a book of importance, especiallyIf he looks at spinning, praising, and being proud; as a form of advertising, whilesatire; As a form of counter declaration, if not everything in thisIssues for the purpose of advertising, there is no doubt that important aspects of it; Consider them as suchadvertisements or counter-advertisements.Then, the research drew attention to the movement of political media professionals from row to row, as did(Kaab bin Zuhair) when he moved from the ranks of the ignorant to the ranks of the Muslims; attributed toAttempts of the pre-Islamic people to preserve the advertising makers, to deprive their opponents of its benefits, asVerb (Abu Sufyan) with (Al-Asha).This modest research has captured; An appropriate number of advertising poets and their poetryAmong them were (Al-Nabigha Al-Dhubyani) and (Al-Asha) - (Maymoon bin Qais) - and (Ka’b bin(Zuhair), (Qais Laila), (Jamil Buthaina), (Kathir Azza), (Maskin Al-Darmi), (Aban bin AbdAl-Humaid), (Abu Nawas), (Mihyar Al-Dailami) and many others who were mentioned in this research